2020
DOI: 10.5430/ijhe.v9n5p283
|View full text |Cite
|
Sign up to set email alerts
|

The Anatomy of Persistence: Remediation and Science Identity Perceptions in Undergraduate Anatomy and Physiology

Abstract: Undergraduate Anatomy and Physiology (A&P) courses are gateway courses nursing and allied health students must pass before progressing through their academic programs. Many students need to retake the course to receive grades acceptable to progress in their programs, but identifying students at risk of failure may help instructors extend support. In this study, we examined self-efficacy and science identity as potential predictors of student success in these courses, and, by extension, a potential way to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
(82 reference statements)
0
5
0
Order By: Relevance
“…Royse et al. ’s ( 2020 ) investigation of student success in A&P courses further bolsters this recommendation. In finding that science identity most strongly predicted A&P grades, they suggest that “capturing who students believe themselves to be and to which communities they feel that they belong may be an efficacious avenue for motivating and retaining students” ( Royse et al.…”
Section: Discussionmentioning
confidence: 93%
“…Royse et al. ’s ( 2020 ) investigation of student success in A&P courses further bolsters this recommendation. In finding that science identity most strongly predicted A&P grades, they suggest that “capturing who students believe themselves to be and to which communities they feel that they belong may be an efficacious avenue for motivating and retaining students” ( Royse et al.…”
Section: Discussionmentioning
confidence: 93%
“…This science identity is shaped by experiences in learning environments, accessibility of role models, and intersections with other aspects of identity ( 6 ). Identity can be a strong predictor of student persistence in classes ( 7 ) and longer-term persistence in science careers ( 8 ). These effects are stronger in first-generation students and members of historically excluded racial or ethnic groups ( 9 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Human anatomy is a key foundational subject in the education of future health professionals. In the baccalaureate level nursing, allied health, and pre‐health sciences programs, the challenging nature of anatomy courses can create stumbling blocks for the students to advance in their curriculum (Griff, 2016; Schutte, 2016; Royse et al, 2020). In addition, it has been reported that 95% of physician assistant programs in the United States require anatomy as a prerequisite (Snyder et al, 2022).…”
Section: Introductionmentioning
confidence: 99%